(untitled) (MAUSAM, 2003)
Satellite altimeter is a remote sensing sensor providing an integrated picture of the atmosphere and the oceans over large spatial and temporal scales. Though the principle of obtaining altimeter range from the sea surface is simple, quite a good number of corrections have to be applied to the two way travel time. The various sources of errors in the altimeter measurements and the corrections to be applied are described. The potential applications of altimeter measurements in meteorology and oceanography are also discussed.